Grounded Capacitive Sensor Readout Using Improved Guard Driving Circuit - Jirat Chimnoy; Khunanon Karawanich; Pipat Prommee (My University, 2025)
A remote capacitive sensor is necessary in hazardous locations such as liquid boilers and chemical facilities. The connection of the capacitive sensor and coaxial cable is integrated with the readout circuit, encompassing intrinsic noise and parasitic capacitance limitations. This work presents a grounded capacitive sensor with an economical architecture incorporating an RC lowpass filter and an enhanced guard driving circuit. The proposed technique effectively achieves minimal parasitic capacitance and reduced noise at the output. The sensor capacitance can be readily calculated by measuring the output signal's amplitude at the cutoff frequency. Both simulation and experimental findings corroborate its efficacy and precision. The capacitance range can be quantified between 1-100 pF with less than 2% relative errors.
Keywords: Sensor Technology and Measurement Systems